Potensi Wakaf Uang dan Model Pengembangannya: Studi Kasus di Perguruan Tinggi Keagamaan Islam Negeri - Rodame Monitorir Napitupulu; Rukiah Lubis; Hapisuddin Nasution (Jurnal Ilmiah Ekonomi Islam, 2021)
Based on Article 28C of the 1945 Constitution, everyone has the right to education. Educational institutions have an important role in the development and progress of a country. In developed countries, many of the world's best campuses are funded by waqf funds. Meanwhile, in Indonesia, the character is still not comprehensive. This study aims to determine the potential of cash waqf for the development of educational institutions, namely IAIN Padangsidimpuan. This research is a qualitative descriptive study with a case study approach. Data collection was carried out through interviews with informants and searching for various supporting documents from websites and other official publications. The results of this study indicate that the potential for cash waqf for education at IAIN Padangsidimpuan is IDR 368,690,000.00 per month or IDR 4,424,280,000.00 per year. IAIN Padangsidimpuan's Waqf Board is needed as an independent waqf institution to manage waqf funds. The cash waqf development model for education at IAIN Padangsidimpuan uses the second method where some of the waqf funds are used for investment and partly for higher education operational financing. Where sustainable management is important in the development of a cash waqf model for education.